Reflective scanning imaging based on a fast terahertz photodetector - Qiu, Fucheng; Tan, Zhiyong; Fu, Zhanglong; Wan, Wenjian; Li, Mengqi; Wang, Chang; Cao, Juncheng (Optics communications, 2018)
The fast detection of terahertz radiation is recognized as a key technology of terahertz imaging systems. We realize a terahertz imaging system employing a terahertz quantum-well photodetector (QWP) and a terahertz quantum cascade laser (QCL). The detector can rapidly detect the 4.3THz light generated from a pulsed electrically-pump terahertz QCL, which is used as the terahertz source of the imaging system. The object is placed on a rotary scanning platform to realize fast scanning. A practical detection method of the terahertz pulse signal is employed to extract the amplitude information from the terahertz signal and improve the signal-to-noise ratio (SNR) of the system. The electrical and optical performances of the fast terahertz QWP are characterized, and the results show that the terahertz QWP can completely meet the fast detection requirement of the terahertz imaging system. The terahertz images of some invisible objects are obtained with a high contrast within 5 s. The imaging system owns a resolution of 0.3 mm and a circular imaging region with a diameter of 100 mm. An image processing algorithm is applied in this system to solve the noise problem and improve the quality of the images. The imaging results indicate that terahertz QWP has a good application prospect in nondestructive inspection applications and the research of the fast physical or chemistry process.